2019
DOI: 10.1136/bjsports-2018-100278
|View full text |Cite
|
Sign up to set email alerts
|

Wake up and smell the coffee: caffeine supplementation and exercise performance—an umbrella review of 21 published meta-analyses

Abstract: ObjectiveTo systematically review, summarise and appraise findings of published meta-analyses that examined the effects of caffeine on exercise performance.DesignUmbrella review.Data sourcesTwelve databases.Eligibility criteria for selecting studiesMeta-analyses that examined the effects of caffeine ingestion on exercise performance.ResultsEleven reviews (with a total of 21 meta-analyses) were included, all being of moderate or high methodological quality (assessed using the Assessing the Methodological Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
254
3
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 252 publications
(279 citation statements)
references
References 64 publications
7
254
3
15
Order By: Relevance
“…Caffeine is one of the most consumed psychoactive stimulants in the world [1]. The effects of caffeine supplementation on exercise performance have received considerable attention in the literature, and the evidence on its ergogenic effects is well-established [1][2][3]. For example, a recent umbrella review of 21 published metaanalyses reported that caffeine ingestion is acutely ergogenic for aerobic endurance, muscle strength, muscle endurance, power, jumping performance, and exercise speed [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine is one of the most consumed psychoactive stimulants in the world [1]. The effects of caffeine supplementation on exercise performance have received considerable attention in the literature, and the evidence on its ergogenic effects is well-established [1][2][3]. For example, a recent umbrella review of 21 published metaanalyses reported that caffeine ingestion is acutely ergogenic for aerobic endurance, muscle strength, muscle endurance, power, jumping performance, and exercise speed [3].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of caffeine supplementation on exercise performance have received considerable attention in the literature, and the evidence on its ergogenic effects is well-established [1][2][3]. For example, a recent umbrella review of 21 published metaanalyses reported that caffeine ingestion is acutely ergogenic for aerobic endurance, muscle strength, muscle endurance, power, jumping performance, and exercise speed [3]. Despite these established performanceenhancing effects of caffeine, it is also commonly acknowledged that there is a large degree of variation in response to caffeine supplementation between individuals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is one of the most consumed substances in the world [1]. The effects of caffeine on exercise performance have received substantial attention in the literature [1][2][3]. Given its potential as an ergogenic aid, caffeine is also often consumed by athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is the most widely consumed drug worldwide. Several studies and a number of reviews have documented the ergogenic effects of caffeine for aerobic endurance, muscle strength, muscle endurance, anaerobic power, jumping and short‐term high‐intensity exercise performance (Burke, 2008; Davis & Green, 2009; Ganio, Klau, Casa, Amstrong, & Maresh, 2009; Graham, 2001; Grgic et al., 2019; Southward, Rutherfurd‐Markwick, & Ali, 2018). The current leading hypothesis for its mechanism of action is the enhancement of neural drive attributable to the reversal of inhibitory effects of adenosine, by blocking its receptors in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%